2014
DOI: 10.1177/1534735413520035
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeted Effects of Hangeshashinto for Treatment of Chemotherapy-Induced Oral Mucositis on Inducible Prostaglandin E2 Production in Human Oral Keratinocytes

Abstract: Objective. Chemotherapy-induced oral mucositis (COM) is characterized by painful inflammation with prolonged damage that involves the pathological pain-evoking prostaglandin E2 (PGE2). We previously found that gargling with hangeshashinto (HST), a traditional Japanese medicine, was effective for the treatment of COM. However, little is known regarding the mechanisms. Our aim was to identify the active ingredients and clarify the characteristic effects of HST on the PGE2 system. Methods. Prostanoids produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 43 publications
(71 reference statements)
2
74
1
Order By: Relevance
“…A randomized placebo-controlled trial showed that prophylactic systemic administration of indomethacin, a COX-2 inhibitor, significantly lowered the severity and delayed the onset of RIOM (165). In addition, PG E1 and E2 showed improvement in OM induced by RT and CT in few studies; however, their application is still controversial (166–172). …”
Section: Symptomatic Treatment Of Riommentioning
confidence: 99%
“…A randomized placebo-controlled trial showed that prophylactic systemic administration of indomethacin, a COX-2 inhibitor, significantly lowered the severity and delayed the onset of RIOM (165). In addition, PG E1 and E2 showed improvement in OM induced by RT and CT in few studies; however, their application is still controversial (166–172). …”
Section: Symptomatic Treatment Of Riommentioning
confidence: 99%
“…There have been some reports of the favorable effects of Hangeshashinto on chemotherapy and chemoradiotherapy-induced stomatitis (11)(12)(13)(14). As regards EGFR-TKIinduced stomatitis, to the best of our knowledge, there have no reports evaluating oral care in the management of stomatitis to date.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the management of stomatitis, oral care with a mouthwash and gargle liquid containing Azunol was administered to patients treated with afatinib, a second-generation epidermal growth factor receptor (EGFR)-TKI. With regard to Hangeshashinto, a traditional herbal (Kampo) medicine, there have been previous reports of its favorable effects on chemotherapy-and chemoradiotherapy-induced stomatitis (11)(12)(13)(14). Patients who developed stomatitis were treated with a mouthwash containing Hangeshashinto, which has been found to reduce CPT-11induced gastrointestinal tract complications (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…16) As the concentration of baicalin, berberine, baicalein, wogonin, 6-gingerol and 6-shogaol exceeded 0.1 µM in 300 µg/mL HST. 16) We therefore used these six ingredients and examined their effects at concentrations equal (20 µM baicalin, 3.4 µM berberin, 1 µM baicalein, 0.6 µM wogonin, 0.4 µM 6-gingerol and 0.18 µM 6-shogaol) to 300 µg/mL HST 16) on 5-FU-induced upregulation of CXCL1 gene expression. This was significantly attenuated by 1 µM baicalein or 0.4 µM 6-gingerol (Fig.…”
Section: Resultsmentioning
confidence: 99%